2022
DOI: 10.1177/1358863x221086619
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for jugular venous thrombosis in astronauts

Abstract: Background: Thrombosis of the left internal jugular vein in an astronaut aboard the International Space Station was recently described, incidentally discovered during a research study of blood flow in neck veins in microgravity. Given this event, and the high incidence of flow abnormalities, the National Aeronautics and Space Administration (NASA) instituted an occupational surveillance program to evaluate astronauts for venous thrombosis. Methods: Duplex ultrasound of the bilateral internal jugular veins was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…However, whether IJV flow was correctly identified as stagnant or retrograde in the initial cohort study, considering the technological limitations and the relative inexperience of crew as sonographers, is unknown 12 . However, a recent update by Pavela et al 13 also documented retrograde IJV flow in 2/11 astronauts undergoing routine venous ultrasound surveillance in flight.…”
Section: Venous Thrombus In Space: What Do We Know? Vt Pathophysiolog...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether IJV flow was correctly identified as stagnant or retrograde in the initial cohort study, considering the technological limitations and the relative inexperience of crew as sonographers, is unknown 12 . However, a recent update by Pavela et al 13 also documented retrograde IJV flow in 2/11 astronauts undergoing routine venous ultrasound surveillance in flight.…”
Section: Venous Thrombus In Space: What Do We Know? Vt Pathophysiolog...mentioning
confidence: 99%
“…12 Surgery, LKH Südsteiermark, Wagna, Austria. 13 Department Emergency Medicine, University British Columbia, Vancouver, Canada. 14 Amsterdam UMC location University of Amsterdam, Department of Internal Medicine, Section of Nephrology, Amsterdam, The Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Vascular Medicine , Pavela and colleagues report on duplex ultrasound findings in a small cohort of 11 astronauts. 6 They describe abnormal flow characteristics in the internal jugular veins (most prominent on the left) with mild-to-moderate echogenicity of intravenous spontaneous echo contrast, which may be prognostic for thrombus formation and subsequent development of DVT. 6 Such point-of-care ultrasound performed by spaceflight crew members is a valuable tool in the spaceflight medical armamentarium to evaluate and diagnose DVT.…”
mentioning
confidence: 99%
“…6 They describe abnormal flow characteristics in the internal jugular veins (most prominent on the left) with mild-to-moderate echogenicity of intravenous spontaneous echo contrast, which may be prognostic for thrombus formation and subsequent development of DVT. 6 Such point-of-care ultrasound performed by spaceflight crew members is a valuable tool in the spaceflight medical armamentarium to evaluate and diagnose DVT. Studies have previously demonstrated that ultrasound evaluation of several conditions can be performed successfully in microgravity, including pneumothorax 7 and sinus fluid levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation